Current state of nutrition in West Africa and projections to 2030 - CHADARE, FLORA JOSIANE; Affonfere, Marius; Sacla Aidé, Edmond; Fassinou, Finagnon Toyi Kévin; SALAKO, Kolawolé Valère; Pereko, Kingsley Kwadwo Asare; Deme, Bara; Failler, Pierre; Glèlè Kakaï, Romain Lucas; ASSOGBADJO, ACHILLE EPHREM (My University, 2022)
The rapid growth of the human population in West Africa makes malnutrition a pressing issue. This paper highlights the predicted nutritional issues in West Africa by 2030. Data were extracted from the FAOSTAT 2019 database and national nutritional reports. Countries were clustered based on the prevalence of different forms of malnutrition. Trends in the different forms of malnutrition were used to estimate nutritional issues in West Africa by 2030 for each country. Four clusters of countries were identified based on malnutrition indicators. These clusters are different in terms of the prevalence of childhood overweight (cluster 1), stunting (cluster 2), anemia (cluster 3) and wasting (cluster 4). Overall, most countries are not on track in meeting global targets of addressing malnutrition by 2030, especially for anemia.
Keywords: Stunting; Wasting; Anemia; Overweight; Nutritional trends